2016
DOI: 10.1039/c6gc00339g
|View full text |Cite
|
Sign up to set email alerts
|

Polymer grafted layered double hydroxides (LDHs-g-POEGMA): a highly efficient reusable solid catalyst for the synthesis of chromene incorporated dihydroquinoline derivatives under solvent-free conditions

Abstract: Chromene incorporated dihydroquinolines are synthesized using highly active air stable and recyclable LDHs-g-POEGMA as catalyst in green procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…XRD patterns for LDH and LDH/Tris/Pd are shown in Figure . A comparison between XRD pattern of synthesis LDH and those previously reported, established a successful synthesis of CaAl‐layered double hydroxides. In other words, the study of XRD pattern of LDH/Tris/Pd showed the tetragonal phase of the catalyst and indicated that the coordinating Tris didn't change the crystallinity of the LDH.…”
Section: Resultssupporting
confidence: 52%
“…XRD patterns for LDH and LDH/Tris/Pd are shown in Figure . A comparison between XRD pattern of synthesis LDH and those previously reported, established a successful synthesis of CaAl‐layered double hydroxides. In other words, the study of XRD pattern of LDH/Tris/Pd showed the tetragonal phase of the catalyst and indicated that the coordinating Tris didn't change the crystallinity of the LDH.…”
Section: Resultssupporting
confidence: 52%
“…Recently, a new promising class of inorganic layered materials, e.g., layered double hydroxides (LDHs), have been attracting much attention because of their wide applications in catalysts, catalyst precursors, anion exchangers, re retardants, hydrogenation reaction, acid absorbents, bioactive nanocomposites, electroactive and photoactive materials, etc. [6][7][8][9][10] Layered double hydroxides (LDHs), also known as anionic or hydrotalcite-like clays, are a class of lamellar compounds having overall charge neutrality due to the existence of positively charged brucite-like hydroxide layers with typical thickness 0.48 nm and hydrated exchangeable anions located in the interlayer gallery. 6 The positive charge of the brucite-like layers arises from the partially isomorphous substitution of trivalent cations for divalent metal ones.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectrum of Mg 3 Al−ILs−C n −LaW 10 ( n =4, 8, 12) also exhibits C−H stretching vibrations at 2930 and 2856 cm −1 , which are due to the alkyl chain −CH 2 and −CH 3 groups, and a C=N stretching band at 1658 cm −1 because of the imidazole of ILs. Additionally, bands in the 1030–1045 cm −1 region were observed for the Mg 3 Al−ILs−C n −LaW 10 ( n =4, 8, 12) samples, which are assigned to the vibration of the Si−O−M bond (M=Al, Mg) . It should be noted that the FTIR spectrum of Mg 3 Al−NO 3 shows a stretching band at 1384 cm −1 , which is assigned to the N−O bond vibration of NO 3 − (see the Supporting Information, Figure S1); this band disappears in the corresponding FTIR spectra of Mg 3 Al−LaW 10 and Mg 3 Al−ILs−C n −LaW 10 ( n =4, 8, 12), which indicates the complete exchange of NO 3 − by the LaW 10 .…”
Section: Resultsmentioning
confidence: 98%